Preliminary test of an Internet-based diabetes self-management tool. - Armstrong, N; Powell, J (2008)
Self-care is a way of helping the health service to manage the growth in long-term chronic conditions. We developed an Internet-based self-management tool for diabetes following detailed consultations with patients. The Virtual Clinic allows a patient to communicate with their health professionals, find information about their condition and share support and advice with others through peer-to-peer discussions. We conducted a test of the Virtual Clinic with five patients prior to the start of a six-month pilot study to evaluate its feasibility, acceptability and effectiveness. The test session involved an interactive computer-based element followed by a focus group to gather feedback. All five patients were positive about the Virtual Clinic. A user-centred approach to developing an Internet intervention is important to ensure that it will meet patients' needs and that they will be enthusiastic about using it.